Waste Heat Recovery and Utilization of Cement Rotary Kiln Based on Biomass Energy - Enhai Liu; Yine Jiang; Zhanghui Guo; Yingzhi Qian; Ran Yan; Yu Wang; Shuaipeng Wang (BioResources, 2023)
A rotary kiln is a central piece of equipment for the calcination of clinker in the  production of cement. Biomass energy has been applied to rotary kilns, and solar energy has been introduced to assist the energy supply. Coupled optimization results for biomass energy and solar energy applications are compared to the single fossil energy used in the base period. A field survey and statistical analysis and integration of cement clinker production sites in China’s Central Plains Economic Zone revealed a negative linear correlation between the consumption of raw coal in the cement production process and the environmental temperature and humidity parameters of the production lines.  The energy consumption is large and the energy utilization of the system is low, with goodness of fit of R=0.962.  Coupled solar and biomass energy use in the audit period and single energy use in the base period comparison revealed a 19.5% reduction in electricity consumption, a 25.4% reduction in coal consumption and a 4.39% increase in heavy oil consumption. From 2017 to 2020, the average annual consumption cost of electricity and raw coal decreased, while the average annual consumption cost of heavy fuel oil slowly increased. After verification during the audit period, compared with the base period, the total production cost of the case enterprise can be reduced approximately 5.17%, in which the energy cost decreased 0.9%.